IN VIVO STUDY OF EFFICACY OF TRAILOKYASUNDAR RASA IN CHRONIC MYELOID LEUKEMIA - Golecha, *Paras Dilipkumar; Sathe, Ninad; Pargunde, Sheela; Kurve, Siddhisha (International Journal of Ayurveda and Pharma Research, 2018)
Trailokyasundar rasa is one of the Rasakalpa which is explained in Rasaratnasamucchaya, and is suggestive of its efficacy in Pandu roga. Pandu roga is a Pitta pradhanavyadhi in which Rasadhatu and raktadhatu are mainly affected. According to modern texts, all disorders of vitiated digestion, absorption and assimilation can be considered under Pandu. According to modern texts, all disorders of vitiated digestion, absorption and assimilation can be considered under Pandu. Therefore, it can be said that Pandu is a very broad term comprising various rasa and Raktpradoshajvikara such as anaemia, megaloblastic anaemia, blood disorders, leukemia’s etc. Material and method: On the basis of this information animal models were planned to evaluate the effect of self-prepared test drug. Study duration -1 monthDiscussion and results: The activity of Trailokyasundar rasa is highly significant by reducing tumour volume and growth inhibition in animal models of chronic myeloid leukemia. On the 29thday of the experiment tumour size of the control group was 20.05 mm. comparatively in the study group, mean tumour size was of 5.26 mm. Also it prevented decrease in the platelet count and Hb% as compared to untreated mice of CML. Rate of increment of WBC’s was also comparatively reduced in Trailokyasundar rasa treated mice.